Supplementation of standard antibiotic therapy with oral probiotics for bacterial vaginosis and aerobic vaginitis: a randomised, double-blind, placebo-controlled trial. Issue 1 (December 2015) - Heczko, Piotr; Tomusiak, Anna; Adamski, Paweł; Jakimiuk, Artur; Stefański, Grzegorz; Mikołajczyk-Cichońska, Aleksandra; Suda-Szczurek, Magdalena; Strus, Magdalena
Abstract Background This multicentre, randomised, double-blind, placebo-controlled trial was performed to determine whether the use of oral probiotic preparation (prOVag®) containing threeLactobacillus strains together with standard metronidazole treatment and also targeted antibiotic treatment (following the failure of metronidazole therapy) could reduce the recurrence rates of bacterial vaginosis (BV) and aerobic vaginitis (AV). Methods Patients at private gynaecological clinics in Poland with histories of recurrent BV/AV and current symptoms were randomly allocated to receive metronidazole and probiotic or placebo, and assessed monthly on visits II and III-V. The total number of study visits was 5–6 (I, II, II bis – if applicable, III, IV, V). One probiotic or placebo capsule was administered with metronidazole/targeted antibiotic twice daily for 10 days; during follow up, patients took one capsule daily for 10 days perimenstrually. Clinical examination and vaginal swabbing were performed at each visit. Primary outcomes were clinical or microbiological BV/AV recurrence and probiotic safety. Secondary outcomes were vaginal pH, Nugent score, andLactobacillus counts in the vaginal microbiota. Safety analysis was performed in 578 (probiotic, n = 285; placebo, n = 293) 18–50-year-old women who were randomised. Results BV/AV was confirmed microbiologically in 241 (probiotic, n = 118; placebo, n = 123) participants, who continued the trial. Data from 154 (probiotic, n = 73; placebo, n = 81) participants who completed the study were analysed to determine the efficacy of prOVag. Additional analyses included 37 (probiotic, n = 22; placebo, n = 15) participants who received targeted antibiotics and probiotics or placebo. prOVag lengthened the time to clinical relapse of BV/AV symptoms up to 51 % (p < 0.05) compared with placebo; AV relapse was delayed by up to 76 % (p < 0.05). Probiotic use also reduced and maintained low vaginal pH and Nugent score, and increased vaginalLactobacillus counts following standard treatment. Conclusion This study demonstrated that oral probiotics lengthened remission in patients with recurrent BV/AV and improved clinical and microbiological parameters. Trial registration NCT01993524 ; 20 November 2013.